Development of Scale to Measure Sunflower Farmers’ Perception on Public and Private Extension Systems (Indian Journal of Extension Education, 2022)
To measure the perception of sunflower farmers on public and private extension systems, a scale was developed with Likert’s summated rating technique during 2021-22. A list of 35 and 41 items regarding public and private extension systems, respectively were sent to 300 experts for their relevancy using google forms and personal follow up. Based on 45 experts’ ratings, the relevancy percentage (RP), Relevancy Weightage (RW) and Mean Relevancy Scores (MRS) were estimated. Eighteen and 22 items with RP > 70, RW > 0.70 and overall MRS > 2.39 and > 2.44 were considered for item analysis regarding public and private extension systems, respectively. These items were administrated to 60 farmers. Based on t-value (>1.75) resulting from item analysis, 13 and 17 items were finally retained in the public and private extension systems scales, respectively. The Cronbach’s alpha value was 0.71 and 0.74, Guttman split half method was 0.70 and 0.74 and Spearman Brown coefficient was found to be 0.70 and 0.75 regarding public and private extension systems, respectively which showed high reliability. The validity and reliability measures of the scales indicated the precision and consistency.